Formulation of dark chocolate as a carrier to deliver eicosapentaenoic and docosahexaenoic acids: Effects on product quality - Toker, Omer Said; Konar, Nevzat; Palabiyik, Ibrahim; Pirouzian, Haniyeh Rasouli; Oba, Sirin; Polat, Derya Genc; Poyrazoglu, Ender Sinan; Sagdic, Osman (ELSEVIER SCI LTD, 2018)
In this study, dark chocolate enriched with EPA (eicosapentaenoic acid) and DHA (docosahexaenoic acid) was developed using various forms and origins. Quality characteristics such as physical, thermo-gravimetric, rheological, textural and sensory properties of chocolates were investigated. The highest EPA/DHA stability was determined in samples prepared by free-flowing powder and microencapsulated forms of omega-3 fatty acids (FA). The L* and C* values varied from 32.16-33.37 and 7.45-8.09, respectively for the all samples. Hardness values ranged between 6422 and 8367 N and the use of EPA/DHA in the triglyceride form caused softer chocolate whereas control sample was the hardest sample. Melting and rheological properties were not significantly affected by the studied EPA/DHA sources (P < 0.05). Microencapsulated EPA/DHA added chocolate was the most preferred source whereas sample with algae oil showed the lowest acceptability. According to the results, dark chocolate can be used for delivering omega-3 FA by considering their origin and physical form.
Keywords: Chocolate; EPA; DHA; Omega-3; Quality; CARDIOVASCULAR-DISEASE; RHEOLOGICAL PROPERTIES; ANTIOXIDANT CAPACITY; BULK SWEETENERS; FUNCTIONAL FOOD; PARTICLE-SIZE; OMEGA-3-FATTY-ACIDS; MILK; CONSUMPTION; IMPACT; Chemistry; Food Science & Technology; Nutrition & Dietetics